2020
DOI: 10.1017/s0033291720002251
|View full text |Cite
|
Sign up to set email alerts
|

Online psychological interventions to reduce symptoms of depression, anxiety, and general distress in those with chronic health conditions: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Over the past 15 years, there has been substantial growth in web-based psychological interventions. We summarize evidence regarding the efficacy of web-based self-directed psychological interventions on depressive, anxiety and distress symptoms in people living with a chronic health condition. Method We searched Medline, PsycINFO, CINAHL, EMBASE databases and Cochrane Database from 1990 to 1 May 2019. English language papers of randomized controlled trials (usual care or waitl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 116 publications
6
44
2
Order By: Relevance
“…school-based mental health programmes for students) may be cost effective (Holmes et al ., 2018 ), and multi-channel interventions and treatments (e.g. film-based education, internet-based and telephone-based helplines and mental health mobile apps) look forward to development and improvement (Kang et al ., 2020 ; White et al ., 2020 ; Goodwin et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…school-based mental health programmes for students) may be cost effective (Holmes et al ., 2018 ), and multi-channel interventions and treatments (e.g. film-based education, internet-based and telephone-based helplines and mental health mobile apps) look forward to development and improvement (Kang et al ., 2020 ; White et al ., 2020 ; Goodwin et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following the proposal by Wang et al ( 2020a ), there is a need for online mental health training for the professionals. Two metanalysis carried out before the COVID showed that online psychological interventions showed effect in reducing depressive symptoms in non-depressed population (Rigabert et al, 2020 ) and in reducing symptoms of anxiety, distress and depression in chronic health populations (White et al, 2020 ). In this sense, online psychological treatments should be improved in order to respond the need for treatment after confinement periods.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that guided iCBT can be as effective as face-to-face CBT for a broad range of somatic and mental conditions ( Andersson et al, 2014 ; Carlbring et al, 2018 ; Bendig et al, 2018 ) and that (guided) iCBT has an effect on a broad range of outcomes ( Buhrman et al, 2016 ; Ljótsson et al, 2014 ; Macea et al, 2010 ; Mehta et al, 2019 ; Van Beugen et al, 2014 ; White et al, 2020 ). It was shown to attain significant improvements in psychological outcomes (e.g., depressive mood, anxious symptoms [ Buhrman et al, 2016 ; Mehta et al, 2019 ; Van Beugen et al, 2014 ]), disease-related physical outcomes (e.g., pain, fatigue, and/or headache [ Buhrman et al, 2016 ; Van Beugen et al, 2014 ]), and impact on daily life outcomes (e.g., quality of life [ Van Beugen et al, 2014 ]) among patients with chronic somatic (pain) conditions when compared to various control groups.…”
Section: Introductionmentioning
confidence: 99%
“…Guided internet-based interventions appear to have larger effects than unguided internet-based interventions in mental health conditions ( Baumeister et al, 2014 ; Karyotaki et al, 2021 ; Richards and Richardson, 2012 ), with limited evidence that intensive guidance may be equally effective as less intensive guidance ( Baumeister et al, 2014 ). The efficacy of therapist guidance in somatic conditions and chronic pain appears to be less consistent, with some studies showing superiority of guided interventions and others finding similar effects of guided and unguided interventions (e.g., Buhrman et al, 2016 ; Mehta et al, 2019 ; Van Gils et al, 2016 ; Vugts et al, 2018 ; White et al, 2020 ). There are differing accounts on the importance of the qualification of coaches.…”
Section: Introductionmentioning
confidence: 99%